A Study on the Perception of Source Credibility of Women Celebrities Endorsement in Television Advertisements - Mahalakshmi.G, P. R. Shini (Journal of Informatics Education and Research, 2024)
Advertising is a way of communication to encourage an audience to make purchase decisions about a product or service and conveying information to viewers. It is considered as a vital and essential element for the economic growth of the marketers and business. Celebrity in a brand is the most important recognition of a brand. The products endorsed by celebrities are considered as a center of attraction and the highest appealing factor among the audience. This study tends to analyze the perception of source credibility of women celebrities with regard to Television Advertisement The present study concentrates on analyzing the source credibility of women celebrities with regard to the products endorsed in television. The study also evaluates the perception of consumers towards brands endorsed by women celebrities. The major findings of the study explain that Source Credibility factors such as Professionalism, Virtuousness, Physical Attractiveness and Trustworthiness of women celebrity highly persuades consumer purchase patterns. DOI: https://doi.org/10.52783/jier.v4i3.1394